2010
DOI: 10.1007/s10517-010-0898-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in β-Endorphin Level in the Cingulate Cortex in Rats after Peripheral Loperamide and Methylnaloxone Administration at Rest and during Emotional Stress

Abstract: β-Endorphin content in the extracellular space of rat cingulate cortex was measured using intravital microdialysis followed by ELISA. Intragastric administration of μ-opioid ligands loperamide and methylnaloxone not crossing the blood-brain barrier produced different effects on β-endorphin level: loperamide reduced and methylnaloxone significantly increased the release of β-endorphin into the extracellular space of rat cingulate cortex. Emotional stress caused by immobilization resulted in slight increase in β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 6 publications
(7 reference statements)
0
9
0
Order By: Relevance
“…β-endorphin binds with high affinity to µ and δ-opioid receptors (Williams et al 2001), and blockade of these receptors by non-specific or specific antagonists reduces the conditioned effects of ethanol (Cunningham et al 1995; 1998; Kuzmin et al 2003; Bechtholt & Cunningham, 2005; Dayas et al 2007; Marinelli et al 2009; Gremel et al 2011; Pastor et al 2011). NLX, at the doses used in our study, acts as a non-selective opioid receptor antagonist of µ and δ receptors that are expressed in regions innervated by β-endorphin neurons, such as the ventral tegmental area (VTA), anterior cingulate cortex (ACC), nucleus accumbens and amygdala (Gutstein and Akil, 2001; Mansour et al 1996; Sudakov et al 2010; Tseng et al 2013). Previous research from our lab has suggested that the conditioned motivational response that normally maintains cue-induced ethanol-seeking behavior depends on µ-opioid receptors within the VTA (Bechtholt and Cunningham, 2005) and the ACC (Gremel et al 2011), but not the nucleus accumbens (Bechtholt and Cunningham, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…β-endorphin binds with high affinity to µ and δ-opioid receptors (Williams et al 2001), and blockade of these receptors by non-specific or specific antagonists reduces the conditioned effects of ethanol (Cunningham et al 1995; 1998; Kuzmin et al 2003; Bechtholt & Cunningham, 2005; Dayas et al 2007; Marinelli et al 2009; Gremel et al 2011; Pastor et al 2011). NLX, at the doses used in our study, acts as a non-selective opioid receptor antagonist of µ and δ receptors that are expressed in regions innervated by β-endorphin neurons, such as the ventral tegmental area (VTA), anterior cingulate cortex (ACC), nucleus accumbens and amygdala (Gutstein and Akil, 2001; Mansour et al 1996; Sudakov et al 2010; Tseng et al 2013). Previous research from our lab has suggested that the conditioned motivational response that normally maintains cue-induced ethanol-seeking behavior depends on µ-opioid receptors within the VTA (Bechtholt and Cunningham, 2005) and the ACC (Gremel et al 2011), but not the nucleus accumbens (Bechtholt and Cunningham, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The observed effect was probably related to an increase in the density of μ-opioid receptors in the brain cortex and midbrain [4] and stimulation of δ-endorphin release under these conditions [9]. It can be hypothesized that the anxiolytic effect of δ-opioid receptor antagonist ICI 174.864 is associated with activation of the central compartment of the δ-opioid system.…”
Section: Resultsmentioning
confidence: 98%
“…Our previous experiments showed that agonists and antagonists of peripheral μ-opioid receptors have opposite effect on pain sensitivity, feeding behavior, anxiety, and locomotor activity of animals [8,9]. However, the role of the peripheral compartment of the δ-opioid system in emotionality and anxiety remains unclear.…”
mentioning
confidence: 99%
“…These changes are accompanied by an increase in the number of P-opioid receptors [3,4]. The antianxiety effect of methylnaloxone is probably related to these changes.…”
Section: Resultsmentioning
confidence: 98%